2019
DOI: 10.1002/icd.2160
|View full text |Cite
|
Sign up to set email alerts
|

Development of executive function skills: Examining the role of teachers and externalizing behaviour problems

Abstract: The current study examined the effect of children's positive relationships and interactions with their teachers and the development of executive function (EF) skills in first grade. A primary objective was to examine externalizing behaviour problems (EBPs) as a potential moderator of the link between teacher–child relationships and interactions and EF skills. Participants for the study included 1,364 first‐grade children (48.3% female, M age = 7.02 years, 80.4% White) drawn from the National Institute of Child… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
4
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(3 citation statements)
references
References 71 publications
0
4
0
Order By: Relevance
“…As a result, the CLASS transforms theoretical concepts articulated in the TTI framework and provides an operational tool that is instrumental in observing and quantifying the TSI, facilitating its application in professional development, teacher training, and research. In agreement with the TTI framework (and the CLASS), numerous observational studies have consistently demonstrated a correlation between the quality of TSIs and children's WM skills [82][83][84][85]. A recent meta-analysis [10] informed further regarding the strength of these associations, revealing small-to-medium overall effect sizes.…”
Section: Teacher-student Interactionmentioning
confidence: 70%
“…As a result, the CLASS transforms theoretical concepts articulated in the TTI framework and provides an operational tool that is instrumental in observing and quantifying the TSI, facilitating its application in professional development, teacher training, and research. In agreement with the TTI framework (and the CLASS), numerous observational studies have consistently demonstrated a correlation between the quality of TSIs and children's WM skills [82][83][84][85]. A recent meta-analysis [10] informed further regarding the strength of these associations, revealing small-to-medium overall effect sizes.…”
Section: Teacher-student Interactionmentioning
confidence: 70%
“…The proposed framework organises TSI into three domains reflecting distinct features of these interactions; namely, emotional support (for instance, acknowledging children's emotions and experiences, and sensitively responding to them), classroom organisation (for instance, clarifying the rules and expectations), and instructional support (for instance, asking open-ended questions) (Downer et al, 2010;Hamre et al, 2013). In agreement with the framework, numerous observational studies have shown a correlation between the quality of TSI at the classroom level (i.e., emotional, instructional, and organisational support) and children's EF/SR skills (e.g., Cadima et al, 2015b;Crockett et al, 2017;Acar et al, 2018;Goble et al, 2019; for a review, see Cumming et al, 2019). For instance, a recent meta-analysis (Vandenbroucke et al, 2017(Vandenbroucke et al, , 2018 informs further regarding the strength of the correlations between these concepts, and overall effect sizes indicate small to medium associations between TSI and working memory, and a small association with inhibition, but not cognitive flexibility.…”
Section: Introductionmentioning
confidence: 72%
“…Two articles in the Special Issue focused on EF within the school context. In one of these articles, Goble, Nauman, Fife, and Blalock () investigated teacher–child relationships, externalizing behaviour problems (EBPs), and children's EF skills using data from the National Institute of Child Health and Human Development Study of Early Child Care and Youth Development. Somewhat surprisingly, EBPs were not related to change in working memory or inhibitory control, which the authors speculated may be due to their study's focus on change in EF from 54 months to first grade and the fact that EBP was dichotomized in their study using clinical cut‐offs.…”
Section: Other Relevant Contextsmentioning
confidence: 99%